2021
DOI: 10.1080/19317611.2021.1958040
|View full text |Cite
|
Sign up to set email alerts
|

The Elephant in the Room – A Critical Interpretive Synthesis of Older Adults’ Sexuality

Abstract: Objectives: This study aimed to explore past studies that have focused exclusively on the sexuality of adults older than 65 from a positive public health approach. Methods: We performed a critical interpretive synthesis, starting with the literature review on sexual behaviors in later life, adding policy documents on aging sexuality, and bringing new perspectives. Results: Older adults continue to be sexually active. Healthcare professionals lack knowledge and communication skills surrounding aging sexuality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Healthcare professionals therefore need training to increase their comfort with raising this topic with older patients, and sexual education programs should focus on different ages, not just on youth 11 . Policies, practice, research, and society all influence each other 9 , and a more positive approach to sexuality in older adults is needed to increase acceptance of sexuality in later life. Our findings provide further support for previous recommendations that healthcare professionals need training to reassess their beliefs about sexuality in later life and improve their communication with older patients on this topic 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Healthcare professionals therefore need training to increase their comfort with raising this topic with older patients, and sexual education programs should focus on different ages, not just on youth 11 . Policies, practice, research, and society all influence each other 9 , and a more positive approach to sexuality in older adults is needed to increase acceptance of sexuality in later life. Our findings provide further support for previous recommendations that healthcare professionals need training to reassess their beliefs about sexuality in later life and improve their communication with older patients on this topic 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Older adults have expressed a desire for healthcare providers to pay more attention to sexuality in later life 7 and provide help if needed 8 . However, studies have shown that healthcare professionals lack knowledge and communication skills on aging sexuality 9 , that older patients' sexuality is considered outside the scope of practice 10 , and medicine-based treatment plan regarding sexual dysfunction is recommended to older patients, compared to the therapy treatment plan recommended to younger patients 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, findings suggest that having a fulfilling sexual life is beneficial for health and quality of life (T. J. Flynn & Gow, 2015 ; Smith et al., 2019 ; Willie-Tyndale et al., 2021 ; Wright et al., 2019 ). Maintaining sexual desire and sexual satisfaction in older age was linked with multiple dimensions of well-being (Buczak-Stec et al., 2019 ; Jackson et al., 2019 ; D. M. Lee, Vanhoutte, et al., 2016 ; Smith et al., 2019 ) and successful aging (Štulhofer et al., 2018 )., thus underlining the importance of adopting a more positive approach toward sexuality and aging, namely including sexual health and pleasure, for promoting well-being in later adulthood (Cismaru-Inescu et al., 2022 ; Sladden et al., 2021 ; Syme et al., 2019 )…”
Section: Introductionmentioning
confidence: 99%